Correlation between hyperbilirubinemia risk and immune cell mitochondria parameters in neonates with jaundice - Yingying Wang; Hongwei Wang; Qiang Zhang; Shanshan Li; Yiping Mao; Jiajin Lu; Yeqin Shen; Yaping Han (Frontiers Media S.A., 2023)
PurposeTo explore the correlation between mitochondria parameters of immune cells and hyperbilirubinemia risk in hospitalized neonates with jaundice.MethodsThis retrospective study included jaundiced neonates born between September 2020 and March 2022 at Shaoxing Keqiao Women & Children's Hospital. The neonates were divided into low, intermediate-low, intermediate-high, and high-risk groups according to the hyperbilirubinemia risk. The purpose parameters including percentage, absolute count, mitochondrial mass (MM), and single-cell MM (SCMM) of peripheral blood T lymphocytes detected by flow cytometry were collected.ResultsFinally, 162 neonates with jaundice (47, 41, 39, and 35 with low, intermediate-low, intermediate-high, and high-risk) were included. CD3+ SCMM was significantly higher in the high-risk group compared with the low and intermediate-low-risk groups (both P < 0.0083), CD4+ SCMM was significantly higher in the high-risk group compared with the three other groups (all P < 0.0083), and CD8+ SCMM was significantly higher in the intermediate-low and high-risk groups compared with the low-risk group (both P < 0.0083). CD3+ (r = 0.34, P < 0.001) and CD4+ (r = 0.20, P = 0.010) SCMM positively correlated with bilirubin levels.ConclusionsThe mitochondrial SCMM parameters differed significantly among jaundiced neonates with different hyperbilirubinemia risks. CD3+ and CD4+ T cell SCMM values were positively correlated with the serum bilirubin levels, and might correlated with hyperbilirubinemia risk.